Emerging non-thermal technologies for decontamination of Salmonella in food. (June 2021) - Kaavya, Rathnakumar; Pandiselvam, R.; Abdullah, S.; Sruthi, N.U.; Jayanath, Yasendra; Ashokkumar, C.; Chandra Khanashyam, Anandu; Kothakota, Anjineyulu; Ramesh, S.V.
Abstract: Background: Salmonella infection has become a foremost health issue as it is the causative agent of several foodborne outbreaks. Currently, there is a huge demand for safe, healthy, and nutritious, fresh-like food products. It strongly suggests the food manufacturers to develop appropriate practices like expeditious testing, detection, and inactivation of foodborne pathogens as well as to prevent the pathogen entry into the supply chain. Scope and approach: In this decade, a lot of innovative ideas and technologies have been investigated as a substitute for conventional thermal technologies employed to inactivate foodborne pathogens. This review presents the potential of such technologies for instance, cold plasma, light-emitting diode, ozone, ultrasound, and pulsed electric field in decontaminating the Salmonella in food production and supply chain. These emerging innovative decontamination practices not only ensure the freshness of food but also enhance the microbial safety and quality of a food product. The synergistic effect of the cold plasma technique arrests the pathogenic cells' viability and multiplication. Oxidative response and the free radical generation capability of ozone treatment destroy the bacterial cells and accord antimicrobial activity. Applications of acoustic cavitation mechanism of ultrasound and non-ionizing electromagnetic radiations of UV light progressively inactivate the pathogenic microorganisms. The high-intensity usage of electric field strength by utilizing the electroporation method resulting in microbial cell death. Key findings: The effect of emerging non-thermal technologies and the processing parameters involved in the decontamination have been reviewed comprehensively along with the summary of different food products. A thorough understanding and deep insights into the mechanisms underlying the optimization of the process conditions will pave the way for upscaling these technologies for improved quality and sustaining the nutritional components of the food product. Graphical abstract: Image 1 Highlights: Salmonella induced illness continues to be a major health concern worldwide. Non-thermal technologies exhibit efficient decontamination with less impact on food quality. Oxidative properties of cold plasma and ozone impose detrimental effects on bacterial cell. LED/UV illumination of microbial photosensitizers releases reactive species with cytotoxic effect. Hurdle approach showed enhanced antimicrobial effect on Salmonella.